Fusobacterium necrophorum Promotes Apoptosis and Inflammatory Cytokine Production Through the Activation of NF-κB and Death Receptor Signaling Pathways - Wang, Feng-Feng; Zhao, Peng-Yu; He, Xian-Jing; Jiang, Kai; Wang, Tian-Shuo; Xiao, Jia-Wei; Sun, Dong-Bo; Guo, Dong-Hua (Frontiers in Cellular and Infection Microbiology, 2022)
Fusobacterium necrophorum can cause liver abscess, foot rot in ruminants, and Lemire syndrome in humans, Also, its virulence factors can induce the apoptosis of macrophages and neutrophils. However, the detailed mechanism has not been fully clarified. This study investigated the mechanisms of apoptosis and inflammatory factor production in F. necrophorum–induced neutrophils and macrophages (RAW246.7). After infection of macrophages with F. necrophorum, 5-ethynyl-2'-deoxyuridine labeling assays indicated that F. necrophorum inhibited macrophage proliferation in a time- and dose-dependent manner. Hoechst staining and DNA ladder assays showed significant condensation of the nucleus and fragmentation of genomic DNA in F. necrophorum–infected macrophages，Annexin V (FITC) and propidium iodide (PI) assay confirmed the emergence of apoptosis in the macrophages and sheep neutrophils with F. necrophorum compared with the control. The group with significant apoptosis was subjected to RNA sequencing (RNA-Seq), and the sequencing results revealed 2581 up– and 2907 downregulated genes. Gene Ontology and Kyoto Eecyclopedia of Genes and Genomes analysis of the differentially espressed genes showed that F. necrophorum drove apoptosis and production of inflammatory factors by activating genes related to the Nuclear Factor-κB (NF-κB) and death receptor pathways. Meanwhile, quantitative reverse transcription PCR and Western blot validation results were consistent with the results of transcriptome sequencing analysis. In conclusion, F. necrophorum induced apoptosis and production of pro-inflammatory factors through the NF-κB and death receptor signaling pathway, providing a theoretical basis for further mechanistic studies on the prevention and control of F. necrophorum disease treatment.